2019
DOI: 10.1093/nar/gky1287
|View full text |Cite
|
Sign up to set email alerts
|

Small nucleolar RNAs controlling rRNA processing in Trypanosoma brucei

Abstract: In trypanosomes, in contrast to most eukaryotes, the large subunit (LSU) ribosomal RNA is fragmented into two large and four small ribosomal RNAs (srRNAs) pieces, and this additional processing likely requires trypanosome-specific factors. Here, we examined the role of 10 abundant small nucleolar RNAs (snoRNAs) involved in rRNA processing. We show that each snoRNA involved in LSU processing associates with factors engaged in either early or late biogenesis steps. Five of these snoRNAs interact with the interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 86 publications
(144 reference statements)
0
37
0
Order By: Relevance
“…In most organisms, a small subset of around six snoRNAs participates in rRNA processing, including the box C/D snoRNAs U3, U8, U14 and U22, and the box H/ACA snoRNAs U17 (snR30) and snR10 [92]. Remarkably, at least 18 snoRNAs (16 box C/D and 2 box H/ACA) are involved in rRNA processing in trypanosomatids, which is the highest number ever reported [117]. This is in accordance with the extensive processing required to produce the six independent rRNA species from the LSU precursor in trypanosomatids (Figure 3).…”
Section: Processing and Nucleotide Modifications In Rrnamentioning
confidence: 99%
See 3 more Smart Citations
“…In most organisms, a small subset of around six snoRNAs participates in rRNA processing, including the box C/D snoRNAs U3, U8, U14 and U22, and the box H/ACA snoRNAs U17 (snR30) and snR10 [92]. Remarkably, at least 18 snoRNAs (16 box C/D and 2 box H/ACA) are involved in rRNA processing in trypanosomatids, which is the highest number ever reported [117]. This is in accordance with the extensive processing required to produce the six independent rRNA species from the LSU precursor in trypanosomatids (Figure 3).…”
Section: Processing and Nucleotide Modifications In Rrnamentioning
confidence: 99%
“…This is in accordance with the extensive processing required to produce the six independent rRNA species from the LSU precursor in trypanosomatids (Figure 3). As anticipated, several of these snoRNAs are exclusive to trypanosomatids [117]. In yeast, U3 snoRNA is required for early processing events conducting to 18S rRNA maturation, as it participates in cleavage at A0, A1 and A2 sites [106].…”
Section: Processing and Nucleotide Modifications In Rrnamentioning
confidence: 99%
See 2 more Smart Citations
“…Small nucleolar RNA (snoRNA) is also a class of non-coding RNA, with a length of 60-30nt. As early studies found that snoRNA was mainly located in the nucleoli and was related to the processing and modi cation of rRNA, its function was relatively simple [9][10][11]. However, in recent years, more and more RNA sequencing (RNA-seq) dataset show that snoRNA shows a general trend of high expression in tumors, and some studies show that snoRNA is involved in the occurrence, progression and prognosis of tumors, and may be a kinds of new clinical biomarkers [12][13][14].…”
Section: Introductionmentioning
confidence: 99%